Assessing the Actual Stage of Social and Environmental Reporting of the Companies Listed at Bucharest Stock Exchange - Mihaela Turturea (Journal of Accounting and Management Information Systems (JAMIS), 2016)
Transparency is becoming a worldwide necessity determined by the increasing demand of responsible actors regarding certain justification related to the impact of different entities towards the environment. Within an economic environment described by complexity, continuous change and development our paper aims to provide an image of contemporary reporting practices in a developing country with regard to the inclusion of social and environmental aspects within reporting practices. This paper aims at examining the extent to which the Bucharest Stock Exchange listed companies belonging to premium and standard categories report on CSR and the way stock price evolution can be explained through financial profitability, size, leverage, industry and CSR disclosures. The results achieved show that there is a concern among Romanian listed companies to include environmental and social disclosures in their reporting practices during 2001-2014 analyzed period, a significant number of companies reporting on CSR aspects.
Keywords: Q50; M20; C10; 650; social and environmental reporting; complexity; Bucharest Stock Exchange; CSR disclosure; stock price